Antibiotics and antiseptics for preventing infection in people receiving revision total hip and knee prostheses: a systematic review of randomized controlled trials. Issue 1 (December 2016) - Voigt, Jeffrey; Mosier, Michael; Darouiche, Rabih
Abstract Background Infection rates in revision (second and subsequent) major joint arthroplasty continues to be a significant issue with rates 2–3 times those of primary procedures. The effect of antibiotic and antiseptic prophylaxis on outcomes for this type of surgery has not been adequately reviewed. Methods A systematic search of the main databases for randomized controlled trials (RCTs) evaluating antibiotics and antiseptics was conducted to evaluate the predetermined endpoints of infection. Results There were five (5) RCTs identified that examined the effects of antibiotic and antiseptic prophylaxis on infections after revision total hip arthroplasty [THA] (total of 304 participants) and total knee arthroplasty [TKA] (total of 206 participants). For TKA, preoperative systemic intravenous (IV) antibiotic prophylaxis plus antibiotic cement may be effective in reducing the incidence of infection in revision TKA at 8+ years. These results however should be interpreted with caution due to the significant biases. For revision THA, there is no RCT evidence that antibiotics/antiseptics have any effect on the infection rate. Conclusions There is a lack of high quality data demonstrating an effect of antibiotics or antiseptics on infection rates in revision THA/TKA. Considering the rate of infections in revisions is 2-3X that of primary procedures and; there is a consensus recommendation to use similar antibiotic and antiseptic regimens in both primary and revision procedures, there is a need for high quality studies in revision THA/TKA.